Perencanaan Arsitektur Teknologi pada PT. X - Eric Christopher Sandjaja; Adi Wibowo; Alexander Setiawan (Jurnal Infra, 2015)
PT. X has grown to be a company of papermaking which has several division to run enterprise business processes. Nowadays information system that support enterprise business processes have inadequacy due to fully unintegrated. That information system only support accountancy, whereas another business process mostly use non electronic. Based on that reason, therefore company need analysis and information system design which is enterprise architecture planning framework. Furthermore, exploring company business processes need analysis of business model and business strategy. Thereby evaluating the condition of information technology, the problems faced and the need of information technology in the future.As a result, the design of data architecture, application architecture and technology architecture are made. The design of data architecture for company consist of several sub system. Moreover, the major applications from design of applications architecture are human resource information system, sales and marketing information system, logistic information system, manufacture information system, warehouse and quality control information system, purchasing information system, accounting and finance information system. Technology architecture purpose use client/server architecture pattern and service oriented architecture data services.